2023
DOI: 10.3390/vaccines11010130
|View full text |Cite
|
Sign up to set email alerts
|

An RNA-Based Vaccine Platform for Use against Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis (M.tb), a bacterial pathogen that causes tuberculosis disease (TB), exerts an extensive burden on global health. The complex nature of M.tb, coupled with different TB disease stages, has made identifying immune correlates of protection challenging and subsequently slowing vaccine candidate progress. In this work, we leveraged two delivery platforms as prophylactic vaccines to assess immunity and subsequent efficacy against low-dose and ultra-low-dose aerosol challenges with M.tb H37R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 67 publications
1
20
1
1
Order By: Relevance
“…Indeed, it has been previously shown that RNA vaccine (repRNA-ID91/ID91+GLA-SE) encoding four M. ah antigens produced significant cellular and humoral immune responses leading to reduced bacterial burden (33). The same group showed that repRNA-ID91/ID91+GLA-SE provided similar protection against M. tb infection in mice (29). However, the highest protection generated by this vaccine was when it is used in a prime (RNA)-boost (protein) regimen (29,33).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, it has been previously shown that RNA vaccine (repRNA-ID91/ID91+GLA-SE) encoding four M. ah antigens produced significant cellular and humoral immune responses leading to reduced bacterial burden (33). The same group showed that repRNA-ID91/ID91+GLA-SE provided similar protection against M. tb infection in mice (29). However, the highest protection generated by this vaccine was when it is used in a prime (RNA)-boost (protein) regimen (29,33).…”
Section: Discussionmentioning
confidence: 98%
“…The same group showed that repRNA-ID91/ID91+GLA-SE provided similar protection against M. tb infection in mice (29). However, the highest protection generated by this vaccine was when it is used in a prime (RNA)-boost (protein) regimen (29,33). Beyond design, mRNA vaccines require sufficient immunostimulatory adjuvants to achieve optimal protective efficacy (49, 50).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Excitingly, prime-boost strategy groups that received heterologous RNA-prime, protein-boost or combination immunisations had the greatest reduction in bacterial burden and a unique humoral and cellular immune response profile. Such data represents the first report that repRNA platforms are a viable system for TB vaccines and should be pursued using high-priority Mtb antigens containing CD4 + and CD8 + T-cell epitopes (Larsen et al 2023 ).…”
Section: Introductionmentioning
confidence: 93%
“…Intranasal immunisation with naked mRNA coding for Hsp65 protein also demonstrated significant protection against M.tb in mouse model ( 145 ). More recently, a replicating mRNA-based vaccine coding for a fusion protein comprising 4 M.tb Antigens (Rv3619, Rv2389, Rv3478, Rv1886) formulated with a lipid nanocarrier induced cellular immune response and protection against M.tb and M. avium challenge in mice in a heterologous RNA-prime and protein-boost vaccination protocol ( 146 , 147 ). Of note, a phase I clinical trial evaluating two investigational RNA-based vaccines against TB in BCG-vaccinated volunteers have been launched by BioNTech ( Table 1 ).…”
Section: Interest Of Mrna Vaccine Technology For Tb Hiv and Malariamentioning
confidence: 99%